Optimasi Produksi Kerupuk Rumput Laut UMKM Winanaz Melalui Pembuatan Dan Penerapan SOP Produksi Dan Alat Pengering Berbasis Teknologi Tepat Guna - Maerani Maerani; Hadi Yusuf Faturochman; Pandu Legawa Ismaya; Rini Harningsih; Fadhiya Munggarani; Dina Aulia Nuraeni; Abraham Sebastian; Fikri Dwi Padilah (I-Com: Indonesian Community Journal, 2024)
Quality inconsistency of products produced and long duration of production time are problems that are often encountered in the home industry (MSMEs). This can be due to the lack of standards in the form of SOPs owned and implemented by MSMEs. Long production times are possible because the process used is still conventional. The purpose of this activity is to increase the understanding of MSME members regarding the importance of SOPs and how to make them as well as assistance in the use of appropriate technology-based cracker dryers. Winanaz MSMEs is one of seaweed crackers producers in Pangandaran Regency. The activities carried out in this service include socialization about SOPs, assistance in making Production SOPs, and the use of appropriate technology-based dryers. Indicators of success in this activity are an increase in participants' understanding of SOPs and how to make them, participants' ability to assemble and use appropriate technology-based dryers.